Evaluation of two portable sensors for energy expenditure assessment during high-intensity running - Koehler, K.; de Marees, M.; Braun, H.; Schaenzer, W. (European Journal of Sport Science, 2013)
The correct assessment of individual energy requirements of athletes remains a challenge. Available literature indicates that accelerometry-based sensors underestimated energy expenditure in athletes, especially during high-intensity exercise. The goal of our study was to evaluate two commercially available devices (Actiheart; SenseWear Pro3) during high-intensity running and to identify potential sources of error.